The Southern Voice: Zapatista and the Challenge towards Neoliberal Agenda in a Globalized World - Gultom, Yosua Saut Marulitua; Andara, Namira Naza; Hutauruk, Muhammad David Ferdian (Global South Review, 2025)
The Zapatistas, emerging in the early 1990s in Chiapas, Mexico, advocate for indigenous autonomy, participatory democracy, and social justice, offering a powerful critique of neoliberal globalization. Their decentralized governance model, based on autonomous municipalities known as "caracoles," emphasizes collective consensus, horizontalism, and grassroots self-governance, challenging conventional power structures. This study utilizes qualitative research through literature analysis and frames its discussion within critical perspective. By critiquing neoliberal policies and advocating for indigenous dignity and autonomy, the Zapatistas underscore the detrimental impacts of globalization on marginalized communities, presenting a broader struggle against capitalist exploitation. It explores the Zapatistas’ ideological foundations, strategic resistance to NAFTA, and its critique of neoliberal globalization highlighting its significance for global social movements. The movement’s unique operational model contrasts with Mexico's hierarchical systems, promoting local authority and community empowerment. The Zapatistas' commitment to gender equality, education, healthcare, and improved living standards reflects their vision of a pluralistic and inclusive society. Their slogan, "a world where many worlds fit," continues to inspire contemporary social movements worldwide, advocating for a just and equitable society.